Intraoperative computed tomography imaging for laryngoplasty. Issue 1 (February 2023) - Kawai, Yoshitaka; Mizuta, Masanobu; Tateya, Ichiro; Kishimoto, Yo; Fujimura, Shintaro; Suehiro, Atsushi; Hiwatashi, Nao; Omori, Koichi
Abstract: Objectives: Intraoperative cone beam computed tomography (CBCT) imaging has the potential to facilitate the surgical procedure. The current preliminary retrospective chart review investigated the benefits of intraoperative CBCT during laryngoplasty. Method: This study examined 26 cases that underwent intraoperative CBCT imaging during laryngoplasty, with one patient who counted twice due to first and revision surgery. The visual quality of structures of interest (glottal shape, thyroid cartilage, arytenoid cartilage, and implants) was determined using intraoperative CBCT during laryngoplasty. Each patient also underwent an aerodynamic assessment. Results: CBCT provided unique information, such as surgical landmarks in severe scarring, the subglottal shape, and the rotation angle of the arytenoid cartilage during arytenoid adduction. Nonetheless, 26.9% (7 of 26) of cases were affected by motion artifact, due to the long acquisition time. When motion artifact-negative cases were evaluated, 100% of glottal shape and more than 89% of thyroid cartilage were well visualized. All arytenoids were well-visualized in patients ≥ 50 years of age and without motion artifact, while CBCT failed to visualize the arytenoids in 2 of 4 patients who were < 50 years, due to the lack of calcifications. After medialization surgery, the yields of improved maximal phonation times (MPTs) in the motion artifact-negative and -positive groups were 8.7 sec and 3.4 sec, respectively (p = 0.032; Welch's t test). This comparison indicates intraoperative CBCT would contribute in MPT improvement, if CBCT is taken in measurable quality. Conclusion: The potential benefits of intraoperative CBCT during laryngoplasty were demonstrated. A corollary, prospective study is warranted to further confirmation.